2005
DOI: 10.1099/vir.0.80411-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of West Nile virus entry by using a recombinant domain III from the envelope glycoprotein

Abstract: The envelope glycoprotein located at the outermost surface of the flavivirus particle mediates entry of virus into host cells. In this study, the involvement of domain III of West Nile virus (WNV-DIII) envelope protein in binding to host cell surface was investigated. WNV-DIII was first expressed as a recombinant protein and purified after a solubilization and refolding procedure. The refolded WNV-DIII protein displays a content of b-sheets consistent with known homologous structures of other flavivirus envelo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
103
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 33 publications
1
103
0
4
Order By: Relevance
“…Crystallography data on the ectodomain of the flavivirus E protein revealed three distinct domains (DI, DII, and DIII) (3). The high antagonistic effect of recombinant WNV E DIII protein in blocking WNV infection in both mammalian and mosquito cells strongly suggested that WNV E DIII protein functions as the receptor-binding domain (4) and is responsible for the recognition and attachment to the cellular receptor (5)(6)(7). Importantly, a majority of the neutralizing epitopes have been mapped to the domain III region of the flavivirus E protein (8 -11).…”
Section: W Est Nile Virus (Wnv)mentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallography data on the ectodomain of the flavivirus E protein revealed three distinct domains (DI, DII, and DIII) (3). The high antagonistic effect of recombinant WNV E DIII protein in blocking WNV infection in both mammalian and mosquito cells strongly suggested that WNV E DIII protein functions as the receptor-binding domain (4) and is responsible for the recognition and attachment to the cellular receptor (5)(6)(7). Importantly, a majority of the neutralizing epitopes have been mapped to the domain III region of the flavivirus E protein (8 -11).…”
Section: W Est Nile Virus (Wnv)mentioning
confidence: 99%
“…The soluble WNV E DIII protein was further purified and concentrated as previously described in Ref. 4. Cleavage of the thioredoxin tag was conducted using enterokinase (Invitrogen Life Technologies) following the manufacturer's recommendations.…”
Section: Cloning Expression and Purification Of Recombinant Wnv E Dmentioning
confidence: 99%
“…DII contains a fusion loop at its distal end that is indispensable for virus-cell membrane fusion. The Ig-like C-terminal domain DIII undergoes a major, pH-triggered positional rearrangement essential for fusion, and may also be involved in receptor binding (2,(6)(7)(8)(9)(10)(11)(12). During cell entry of flaviviruses, low endosomal pH triggers a proposed E protein rearrangement cascade, including the dissociation of E dimers and the outward rotation of DII during the repositioning of E monomers into fusion-active trimers (6,9,13).…”
mentioning
confidence: 99%
“…The DIII has been shown with DENV to be involved in virus attachment to Vero cells in culture (Crill and Roehrig, 2001). These binding characteristics have been confirmed using expressed DIII (Chu et al, 2005). The DI contains the E glycoprotein molecular hinge.…”
Section: Flavivirus Immunochemistrymentioning
confidence: 66%